Hot Topics in Infection and Immunity in Children VI - Finn, Adam.; Curtis, Nigel; Pollard, Andrew J.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2010)
Course covers topics in infectious diseases in children and is intended for Pediatric Infectious disease trainees, trainers, and all those who manage children with infections. Each of the chapters in this book is based on a lecture given at the sixth "Infection and Immunity in Children" course, held at the end of June 2008 at Keble College, Oxford. Thus, it is the sixth book in a series that provides succinct and readable updates on just about every aspect of the discipline of Pediatric Infectious Diseases.
Infections in the Immunocompromised -- Host Biomarkers and Paediatric Infectious Diseases: From Molecular Profiles to Clinical Application -- The Epidemiology and Management of Non Typhoidal Salmonella Infections -- Where Does Campylobacter Come From? A Molecular Odyssey -- Why Are Some Babies Still Being Infected with HIV in the UK? -- The Use and Abuse of Antibiotics and the Development of Antibiotic Resistance -- Vaccination Against Varicella: What's the Point? -- What Can We Learn from the Retina in Severe Malaria? -- Epidemiology and Prevention of Neonatal Candidiasis: Fluconazole for All Neonates? -- Current Status of Treatment of Hepatitis B in Children -- Treatment of Neonatal Fungal Infections -- Malaria in Pregnancy and the Newborn -- Adenovirus Infection in the Immunocompromised Host -- Strategies for Global Prevention of Hepatitis B Virus Infection.
Keywords: Immunology; Medical microbiology; Infectious diseases; Virology; Microbiology; Immunology; Medical Microbiology; Infectious Diseases; Virology; Microbiology